Comparative efficacy of infliximab and adalimumab in patients with ankylosing spondylitis - Tatyana Valentinovna Mezenova; V P Tyurin; S Yu Davidyan; N A Kiryukhina; A V Elonakov (Научно-практическая ревматология, 2012)
Objective: to study the comparative efficacy of the genetically engineered biological agents infliximab (INF) and adalimumab (ADA) in patients with ankylosing spondylitis (AS). Subjects and methods. The study included 86 patients with active AS who had failed to achieve remission with the maximal tolerated doses of nonsteroidal anti-inflammatory drugs, sulfasalazine, methotrexate, and glucocorticoids. The patients were divided into 2 groups: 1) 53 patients (mean age 35±9 years, disease duration 13.9±7.5 years) took INF; 2) 33 patients (mean age 35±12 years; disease duration 9.1±6.7 years) received ADA. Therapeutic effectiveness was evaluated by Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), and Ankylosing Spondylitis Disease Activity Score (ASDAS), Bath Ankylosing Spondylitis Functional Index (BASFI), Bath Ankylosing Spondylitis Metrology Index (BASMI) scores, ASsessments in Ankylosing Spondylitis (ASAS) remission criteria, vertebral index changes, laboratory parameters, and HLA-B27 typing. INF was administered at a dose of 3—5 mg/kg body weight (300—400 mg) at 0, 2, and 6 weeks and then every 8 weeks, ADA was given in a dose of 40 mg once every 2 weeks. Therapeutic effectiveness was evaluated every 12 weeks. Results. At 48 weeks of therapy, there was a 50% decrease in BASDAI scores in 64 and 60% of the patients in the INF and ADA groups, respectively. ASDAS dropped in 69% and reached its minimal value in 51% in the INF group; those in the ADA group were 54 and 66%, respectively. The mean BASFI score was almost halved in both INF and ADA groups; its low score was recorded in 67 and 60%, respectively. Both groups showed a significant increase in the spine range of motion after 12 weeks of therapy. By the end of the study, there was a significant improvement of locomotion (BASMI) as compared to the baseline values: from 19.4±8.1 to 13.6±4.8 and from 17.3±6.2 to 15.9±7.3, respectively. According to the ASAS criteria, partial remission was achieved in 69% of the patients receiving INF and in 75% of those taking ADA. There were marked positive laboratory changes. The INF and ADA groups displayed decreases in erythrocyte sedimentation rate (ESR) from 37.7±18.9 to 19.0±16.8 and from 38.3±16.5 to 17.8±18.5, respectively (p<0.001 in both groups) and C-reactive protein (CRP) from 39.8+37.2 to 7.8±24.0 (p < 0.001) and from 23.2±21.2 to 1.0±2.5 (p > 0.13), respectively; and an increase in hemoglobin from 125.9±18.8 to 137.5±20.4 (p < 0.001) and from 129.7±16.2 to 146.3±11.5 (p > 0.10), respectively. Adverse reactions (AR) were found in 37 and 33% in the IFN and ADA groups, respectively. The most common AR (elevated hepatic enzymes) was seen in 11 and 9% in Groups 1 and 2, respectively. Serious ARs that caused to discontinue the use of a drug were observed in only 1 patient receiving INF. In Group 1, 3% of the patients were found to have a lower therapeutic effectiveness requiring that the biological drug be changed for ADA. Conclusion. BASDAI and BASMI scores indicated a more marked clinical response to INF therapy. Both groups showed a rapid decrease in acute-phase inflammatory markers, such as ESR and CRP, and elevated hemoglobin just in the early periods of therapy. Functional improvement in locomotion (in spondylitis, peripheral arthritis) was achieved in both groups. The genetically engineered biological agents were well tolerated.